(untitled) - Williams, Joan C. (Boston Massachusetts, 2017)
This demographic often resents both the poor and the professionals. They don't, however, tend to resent the truly rich, nor are they particularly bothered by income inequality. Their dream is not to join the upper middle class, with its different culture, but to stay true to their own values in their own communities--just with more money. White Working Class is a blunt, bracing narrative that sketches a nuanced portrait of millions of people throughout the world who have proven to be a potent political force.
Keywords: Giới lao động cổ trắng,Working class whites; Hoa Kỳ,United States